Nanomaterials and Their Optical Applications 2003
DOI: 10.1117/12.507364
|View full text |Cite
|
Sign up to set email alerts
|

Template-based growth of V 2 O 5 nanorods by electrodeposition

Abstract: Template-based growth of single crystal V 2 O 5 nanorods by either electrochemical or electrophoretic deposition was studied. Specifically, standard electrochemical deposition from VOSO 4 solution, electrochemically induced deposition by local pH change of VO 2 + solution, and electrophoretic deposition of nanoclusters in V 2 O 5 sol were investigated.From each route, uniformly sized V 2 O 5 n a n o r o d s a b o u t 1 0 µ m in length were grown over large area with nearly unidirectional alignment, but with va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…nanostructures such as nanotubes and nanowires [249,250]. Other liquid phase methods include the electrodeposition and anodization techniques which have also been shown to synthesise V2O5 nanostructures [251][252][253].…”
Section: Methods Of Synthesismentioning
confidence: 99%
“…nanostructures such as nanotubes and nanowires [249,250]. Other liquid phase methods include the electrodeposition and anodization techniques which have also been shown to synthesise V2O5 nanostructures [251][252][253].…”
Section: Methods Of Synthesismentioning
confidence: 99%
“…Martin et al investigated the electrochemical properties of vanadium pentoxide nanorod arrays made by filling vanadium oxide sol into porous polycarbonate (PC) membranes, and reported that nanorod arrays achieved 4 times the capacity of a thin-film electrode. We recently demonstrated single-crystal V 2 O 5 nanorod arrays grown by electrochemical deposition, surface condensation induced by a change of local pH as a result of H 2 O electrolysis, and sol−gel electrophoretic deposition, combined with template growth methods. , Single-crystal V 2 O 5 nanorod-array electrode has 5 times higher energy storage density than sol−gel derived films in a current density of 0.7 A/g. , These results suggest that the specific surface area of electrode is important since the redox or intercalation reactions occur at and near the electrode interface with electrolyte; hence a nanorod array structure is effective for use as a capacitor.…”
mentioning
confidence: 99%